THE ROLE OF MODERN TECHNOLOGY AND COMMUNICATION MEANS IN ENSURING THE FUNCTIONING OF THE PUBLIC FACILITY UNDER THE PREVAILING CIRCUMSTANCES (COVID-19 VIRUS PANDEMICIS A MODEL) AN APPLIED STUDY ON THE JUDICIAL FACILITY IN THE HASHEMITE KINGDOM OF JORDAN - Prof. Suhaib Ahmad Eid Al-Manaseer (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Public administrations are always seeking to adoptmodern methods in managing public facilities in order to ensure that the public facility function regularly and steadily in all circumstances that the state is going through, especially the exceptional ones. Since the public facility in general has the characteristic of its ability to develop and modify at all times, it has become possible to use modern means of communication and employ them in the field of electronic litigation through the adaptation of these means in the field of public judicial facility particularly the remote litigation and the identification of framework concepts for this process, and to inform the public of what this stage is, to reach an applied vision to have an electronic judicial system, aimsto maintain the operation of public facilities in the country regularly and steadily in order to preserve its prestige, since these means are the product of progress, technological revolution and the change in the concepts and tools of communication which the administration can use to develop the concept of the electronic judicial facility to ensure the sustainability of its work in various circumstances and enable it to confront any force majeure that threatens the integrity of its functioning, or the continuity of its work .